Transient experimental and modelling studies of laser-textured micro-grooved surfaces with a focus on piston-ring cylinder liner contacts - Profito,FJ; Vladescu,S; Reddyhoff; Dini,D (Tribology International, 2016)
This paper presents a comparison between the results from numerical modelling and experiments to shed light on the mechanisms by which surface texture can reduce friction when applied to an automotive cylinder liner. In this configuration, textured features move relative to the piston-liner conjunction and to account for this our approach is to focus on the transient friction response to individual pockets as they pass through, and then leave, the sliding contact. The numerical approach is based on the averaged Reynolds’ equation with the Patir & Cheng’s flow factors and the p-θ Elrod-Adams mass-conserving cavitation model. The contact pressures that arises from the asperity interactions are solved simultaneously to the fluid flow solution using the Greenwood and Tripp method. The experimental data is produced using a pin-on-disc set up, in which laser textured pockets have been applied to the disc specimen. Under certain conditions in the mixed and boundary lubrication regimes, both model and experimental results show i) an increase in friction as the pocket enters the contact, followed by ii) a sharp decrease as the pocket leaves the contact, and then iii) a gradual decay back to the pre-entrainment value. From the evidence obtained for the first time from the proposed combined modelling and experimental investigation conducted under carefully controlled conditions, we suggest that these three stages occur due to the following mechanisms: i) a reduction in fluid pressure due to the increased inlet gap, ii) inlet suction as the cavitated fluid within the pocket draws lubricant into the contact, and iii) film thickness decay as oil is squeezed out of the contact. The interplay of these three mechanisms is shown to control the response of micro-textured surfaces und